Amber was Brave, Essie was Smart : The Story of Amber and Essie Told Here in Poems and Pictures / by Vera B. Williams. - Williams, Vera B. (New York : Greenwillow Books, 2001)
A series of poems tells how two sisters help each other deal with life while their mother is working and their father has been sent to jail.
Keywords: Sisters -- Juvenile poetry; Children's poetry, American; Sisters -- Poetry; American poetry